Hand hygiene: knowledge and skill of caregivers in the hematopoietic stem cell transplantation - Daiane Rubinato Fernandes; Fernanda Titareli Merizio Martins Braga; Renata Cristina de Campos Pereira Silveira; Livia Maria Garbin
ABSTRACT Objective: to identify the knowledge and ability of caregivers on hand hygiene in hematopoietic stem cell transplantation. Method: a prospective cross-sectional study. A questionnaire was used to identify the knowledge and it was observed the hygiene technique performance. Data were collected in two units (autologous and allogeneic transplant). Results: the 37 participants recognized the importance of hand hygiene and 95.5% related to removal of dirt or infection prevention. 91.9% stated that it was important to clean their hands with soap and water when entering and leaving the room, and 64.9% understood that it was necessary to apply alcoholic solution after washing. On average, the caregivers scored 6.16 steps, when demonstrating the washing technique and 3.91 steps in the friction with alcoholic solution. Conclusion: although they recognize the importance of the procedure, there are deficits related to the moment and the correct way of doing it, evidencing the need for strategies aimed at improving this process.